2013
DOI: 10.1371/journal.pone.0071816
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of SIX3 is Associated with Clinical Outcome in Lung Adenocarcinoma

Abstract: BackgroundLung cancer is a common cancer and the leading cause of cancer-related death worldwide. SIX3 is a human homologue of the highly conserved sine oculis gene family essential during embryonic development in vertebrates, and encodes a homeo-domain containing transcription factor. Little is known about the role of SIX3 in human tumorigenesis. This study is to assess the expression/function of SIX3 and the significance of SIX3 as a prognostic biomarker in lung adenocarcinoma.MethodsQuantitative real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Study showed that SIX3 might play an important role as a novel suppressor in human lung cancer. SIX3 had potential as a novel prognostic biomarker for patients with lung adenocarcinomas (Mo et al 2013). In our study, transcription factor SIX3 had high cross ratio, indicating that the identification of transcription factors were reliable.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Study showed that SIX3 might play an important role as a novel suppressor in human lung cancer. SIX3 had potential as a novel prognostic biomarker for patients with lung adenocarcinomas (Mo et al 2013). In our study, transcription factor SIX3 had high cross ratio, indicating that the identification of transcription factors were reliable.…”
Section: Discussionsupporting
confidence: 49%
“…SIX3 was a human homologue of the highly conserved sine oculis gene family essential during embryonic development in vertebrates, and encoded a homeo-domain containing transcription factor (Mo et al 2013). Researches were reported that the homeotic protein Six3 was a co-activator of the nuclear receptor NOR-1 and a co-repressor of the fusion protein EWS/NOR-1 in human extraskeletal myxoid chondrosarcomas (Laflamme et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Min-Li Mo et al demonstrated for the first time that SIX3 over-expression repressed a number of oncogenic genes related to proliferation and metastasis during lung carcinogenesis [18]. Furthermore, SIX3 expression was identified to be associated with improved RFS and OS in the early stage of ADC patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, another critical member of SIX family, SIX3, was reported to act as a repressor in ADC cell proliferation and migration. More importantly, SIX3 could remarkably improve overall survival (OS) and progression-free survival (PFS) in early stage ADC patients [18]. To comprehensively explore the effect of different SIX family members in NSCLC, we analyzed relevant datasets and performed a systemic review and a meta-analysis to assess the profile of SIX family members in NSCLC and evaluate their importance as biomarkers for diagnosis and prediction of NSCLC.…”
Section: Backgroundsmentioning
confidence: 99%
“…48 The four most significantly enriched transcription factor families, SIX3, TF2B, TCFF, and ZFHX, have known associations with human cancers. 4952 Of particular interest, dysregulation of two members of the ZFHX family, zinc finger E-box binding homeobox 1 (Zeb1) and zinc finger E-box binding homeobox 2 (Zeb2), has been associated with bladder cancer. 52,53 Overall, the extensive overlap between transcription factor binding sites within genes with differential methylation associated with EUC As and bladder cancer indicates that similar transcription factors may mediate both exposure and disease-related epigenetic effects.…”
Section: Discussionmentioning
confidence: 99%